The Level of Anti-Viral Antigen-Specific Antibodies to EBNA-1 in the Serum of MS Patients Does not Depend on the Severity of the Disease - Ovchinnikova, L. A.; Dzhelad, S. S.; Simaniv, T. O.; Zakharova, M. N.; Gabibov, A. G.; Lomakin, Y. A. (Doklady. Biochemistry and biophysics, 2024)
Multiple sclerosis (MS) is an autoimmune neurodegenerative disease leading to inevitable disability and primarily affecting the young and middle-aged population. Recent studies have shown a direct correlation between the risk of MS development and Epstein–Barr virus (EBV) infection. Analysis of the titer of EBV-specific antibodies among patients with MS and healthy donors among Russian population confirmed that MS is characterized by an increased level of serum IgG binding EBNA-1 (EBV nuclear antigen 1). The number of patients with elevated levels of EBNA-1-specific antibodies does not differ statistically significantly between two groups with diametrically opposite courses of MS: benign MS or highly active MS. It can be assumed that the primary link between EBV and the development of MS is restricted to the initiation of the disease and does not impact its severity.